Real Money Balances: An Omitted Variable from the Production Function?–A Reply - Sinai, Allen; Stokes, Houston H. (The Review of Economics and Statistics, 1975)
ln Q -0.1988 + 0.6922 ln L (2.8) (4.7) + 0.5896 In K 0.0223 In MF (4.3) (0.2) + 0.2106InMc + 0.0018T. (3.7) (0.4) R = 0.986 D.W. = 1.03 The results indicate that the real money balances held by firms seem to have no significant effect on output. The level of money held by consumers retains its significance. These results are again consistent with induced innovation approach but not with the production factor approach.